DEVELOPING WRITING SKILLS:COMPREHENSIVE APPROACHES IN EDUCATION (Ta'limning zamonaviy transformatsiyasi, 2025)
Annotation. Writing is a vital language skill essential for efficient communication, academic performance, and professional competence. In the context of English as a global language, the ability to write fluently has emerged as a critical component in both personal and professional progress. Improving writing skills requires a diverse approach that combines academic ideas and actual implementations. This article looks at complex approaches for improving writing skills, emphasizing their instructional value and practical benefits.